2011
DOI: 10.3344/kjp.2011.24.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Value of Bone Scintigraphy and Single Photon Emission Computed Tomography (SPECT) in Lumbar Facet Disease and Prediction of Short-term Outcome of Ultrasound Guided Medial Branch Block with Bone SPECT

Abstract: BackgroundFacet joint disease plays a major role in axial low-back pain. Few diagnostic tests and imaging methods for identifying this condition exist. Single photon emission computed tomography (SPECT) is reported that it has a high sensitivity and specificity in diagnosing facet disease. We prospectively evaluated the use of bone scintigraphy with SPECT for the identification of patients with low back pain who would benefit from medial branch block.MethodsSPECT was performed on 33 patients clinically suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Prior reports have found that strictly targeting facet joints with increased 99m Tc MDP activity is predictive of a positive response to percutaneous treatment [4][5][6] and that use of bone scans can decrease the number of treated facet joints. 4 However, in the current retrospective review of our institution, this association did not translate into actual clinical practice for patients in whom 99m Tc MDP SPECT/CT examinations were ordered specifically to identify pain generators, mostly by pain physicians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior reports have found that strictly targeting facet joints with increased 99m Tc MDP activity is predictive of a positive response to percutaneous treatment [4][5][6] and that use of bone scans can decrease the number of treated facet joints. 4 However, in the current retrospective review of our institution, this association did not translate into actual clinical practice for patients in whom 99m Tc MDP SPECT/CT examinations were ordered specifically to identify pain generators, mostly by pain physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic co-localization is important because facet joints are anatomically juxtaposed, the number of vertebral bodies is variable, and transitional lumbosacral vertebral bodies are present in 4%-30% of patients. 8 Previously, criteria for active facet joints were either not clearly defined [5][6] or were arbitrarily designated as those greater than the adjacent vertebral body, 4 which could be problematic because vertebral body activity at the levels of degenerative spinal disease is highly variable in our experience. In addition, prior studies have included patients and proceduralists who were not clearly blinded, 4-6 had widely overlapping statistical error measurements between treatment and control groups, 4 and/or used facet joint injections/single medial branch blocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional data on the use of stand-alone SPECT also point in this direction [42][43][44]. In a further publication, however, Lehmann et al [45], in a group of 74 patients, analyzed the relationship between the localization of abnormal tracer uptake in the facet joint and the joint percutaneously treated.…”
Section: Differential Diagnosis Of Pain Associated With the Musculoskmentioning
confidence: 99%